GOOGLE FORMS: ENRICHING ECONOMIC LEARNING THROUGH ACTION RESEARCH - Poobalan , Gurumoorthy; Talip , Roslee; Asman , Junaidi; Syd Ali , Syd Alimulhakim; Abu Bakar , Nur Afifah; Kaliappan , Sukuneswari; Padan , Rosna; Mohd Aris , Aishah (Journal of Islamic, Social, Economics and Development, 2024)
In the contemporary civilization characterized by advanced technology, Google Forms has emerged as a prominent instructional tool widely utilized in educational institutions of the 21st century. This study aimed to enhance students' understanding and memorization competencies to answer the objective questions on paper 1 of the SPM Economics course. Fifth graders from Delima at SMK Raja Jumaat in Port Dickson participated in the research. Monthly school exams and assessments serve as the basis for the first survey. The poll indicated that students spend a lot of time thinking about and answering economic questions incorrectly. The eight weeks of this training are devoted to action planning, with a particular emphasis on an efficient Google Form quiz technique. Its execution involves teaching students all of the subject's chapters systematically, followed by testing them using Google Forms with economic fact quiz questions, actual SPM economics questions (from 2018 to 2022), and SPM Economics Trial questions (2022 to 2023). In this exercise, students will practice for an economic fact quiz until they reach a predetermined goal. Students exhibit enhanced memorization skills in understanding economic topics and display mastery in swiftly and accurately answering objective questions about economics on the post-exam. Google Forms overcomes the economic information comprehension and memory difficulty and improves student performance regularly. It also promotes environmental sustainability by removing paper and preserving resources.